Efektifitas Kombinasi Stimulasi Kutaneus (Stroking Massage) dan Sunflower Oil terhadap Derajat Pruritus Pasien Gagal Ginjal Kronik - Arifin Hidayat; Frana Andrianur; Emmy Putri Wahyuni (JURNAL KEPERAWATAN RAFLESIA, 2023)
Uremic pruritus is a common problem in renal failure patients undergoing hemodialysis (HD program). The purpose of this study was to see the effectiveness of the combination of stroking massage and sunflower oil on the degree of pruritus. This study is a Randomized Controlled Trials (RCT) study with 40 respondents divided into the intervention group (KI) and the control group (KK), where the intervention group was given a combination of cutaneous stimulation and sunflower oil (5 ml of sunflower oil and 7 minutes of stroking massage) given 2 times a week for 3 (three) weeks, while the control group was only given a stroke massage. Demographic data such as age, gender, duration of hemodialysis and access to hemodialysis were assessed using a questionnaire, while the degree of puritus was assessed using the Dynamic Pruritus Score (DPS). The results showed that there was a significant difference between the control group and the intervention group after giving a combination of stroking massage and sunflower oil with p value =0.000. So that giving a combination of stroking massage and sunflower oil can be an alternative to providing nursing care for kidney failure patients undergoing hemodialysis program with uremic pruritus.